Identification of agroforestry systems and practices to model - Palma, J.H.N. (2015)
This report is an output from work-package 6 which contributes to the third objective. Work-package 6 focuses on the field- and farm-scale evaluation of innovation research that have arisen from about 40 agroforestry stakeholder groups created across Europe. Some research, for example tree protection options, are best determined by technical evaluations in the field. However some research questions require a modelling approach to predict, for example, the financial and economic impact of a new practice over a number of years. This report seeks to identify those agroforestry systems and practices which could be usefully assessed using biophysical agroforestry models such as Yield-SAFE (van der Werf et al., 2007) and Hi-sAFe (Talbot, 2011), or bio-economic models such as Farm-SAFE (Graves et al., 2011).